Kajian Protein Hewani Untuk Meningkatkan Kadar Hemoglobin Pada Ibu Hamil : Literatur Review - Safitri, Fira Deananta; Rahmawati, Alfiah; Jannah, Muliatul (POLTEKKES KEMENKES MANADO, 2025)
Background: Optimal nutrition during pregnancy, especially adequate intake of animal protein, is essential for maternal and fetal health. Animal protein provides essential amino acids needed for fetal growth and maternal tissue development, as well as heme iron, which is easily absorbed and supports hemoglobin production. Adequate intake helps prevent fetal growth restriction and supports normal birth weight. Nutritional deficiencies can lead to complications such as anemia, low birth weight, and congenital abnormalities, while overnutrition may also pose risks. Therefore, maintaining a balanced intake of nutrients, including animal protein, is crucial. Objective: This literature review aims to analyze the role and effectiveness of animal protein in increasing hemoglobin levels in pregnant women as a strategy to prevent pregnancy-related anemia. Methods: A systematic review was conducted using articles from PubMed and Google Scholar databases, published between 2014–2024. Keywords used included